The protection last needed: the Krenak Indigenous Agricultural Reformatory and the State Administration of Indians - Corrêa, José Gabriel Silveira (Arquivos do Museu Nacional, 2021)
This text search for the recuperation of the history of an institution created to correct indians called criminous, who functioned in the early years of FUNAI, the Krenak Indigenous Agricultural Reformatory. The reconstitution of this “story” is important in contrast with the easy way that the Reformatory appears in the literature dedicated to indigenous populations and in the literature dedicated to the indigenist politics developed by the Brazilian State. The situation became evident in the stories about the Krenak indian group, identified in the prison area, whose daily life was modified by the institution. The “case” of the reformatory opens too to the possibility of desnaturalize the actions and projects formulated by the state institutions responsible for the protection and/or assistance of Indians. The reformatory experience when compared with the practices of the functionarys of the tutelage institution and demanded to the Indians – probably until today – make possible to revaluate the actions that based the protection of Indians and the domination’s relations established among Indians groups and tutors, in the period of SPI and FUNAI.